SATUREJA KHUZISTANICA JAMZAD ESSENTIAL OIL AND ITS ANTI-CANDIDAL ACTIVITIES AGAINST CLINICAL ISOLATES OF CANDIDA ALBICANS ISOLATED FROM WOMEN WITH CANDIDIASIS - Mohaddese Mahboubi (Infectio, 2019)
Satureja khuzistanica Jamzad is known as antiseptic and analgesic agent in folk medicine. The aim of this investigation was to evaluate the anti-candidal activity of S. khuzistanica aerial parts essential oil against clinical isolates of Candida albicans, which were isolated from women with chronic recurrent candidiasis. For this purpose, the chemical composition of hydro-distilled essential oil was determined by GC and GC-MS analysis. Then, the anti-candidal activity of essential oil and its main component (carvacrol) were determined. Carvacrol (94.1%) was the main component of essential oil, followed by β-bisabolene, p-cymene and γ-terpinene. S. khuzistanica essential oil had strong anti-candidal activity against clinical isolates of C. albicans via inhibition of germ tube formation and induction the huge punctures in the cytoplasmic structures. The cell membranes were intact in presence of essential oil or carvacrol. S. khuzistanica essential oil as the main source of carvacrol can be used for treatment of C. albicans related infections